Toward a Qur'anic Ethics of Digital Self-Presentation: M. Quraish Shihab's Interpretation of Q. 31:18 and Generation Z's Flexing Culture: Etika Qur'ani tentang Presentasi Diri di Ruang Digital: Penafsiran M. Quraish Shihab terhadap Q.S. Luqman (31): 18 dan Budaya Flexing Generasi Z - Erliani Syafitri Nasution; Abdul Halim (Institut Agama Islam Negeri Kerinci, 2026)
The proliferation of flexing culture on social media has intensified the tension between digital self-presentation and the Islamic ethical value of tawāḍuʿ (humility). This study aims to examine the typology of flexing practices among Generation Z in Padangsidimpuan City and to explore the relevance of M. Quraish Shihab’s interpretation of Q. 31:18 in understanding this contemporary phenomenon. Employing a qualitative research design with a phenomenological approach, the study draws on in-depth interviews with 28 participants, complemented and validated through netnographic observation. The findings identify four dominant forms of flexing: location flexing, achievement flexing, material-possession flexing, and self-archiving flexing. Psychosocially, these practices are driven by the Fear of Missing Out (FOMO) and the pursuit of social recognition within digital environments. The study further reveals a significant gap between individuals’ understanding of Islamic ethical values and their actual online behavior, a discrepancy shaped by peer influence and the algorithmic dynamics of social media platforms. Moreover, the analysis demonstrates that the concepts of tushaʿir, mukhtal, and fakhūr, as articulated in Tafsir Al-Misbah, provide a compelling interpretive framework for understanding manifestations of digital arrogance among Generation Z. The study concludes that M. Quraish Shihab’s exegetical thought remains highly relevant as a foundation for contemporary digital ethics and proposes a model of tawāḍuʿ-based digital literacy to foster the moral and spiritual well-being of young people in the digital age.